Derivatives of montanine-type alkaloids and their implication for the treatment of Alzheimer's disease: Synthesis, biological activity and in silico study. (1st November 2021) - Maafi, Negar; Pidaný, Filip; Maříková, Jana; Korábečný, Jan; Hulcová, Daniela; Kučera, Tomáš; Schmidt, Monika; Shammari, Latifah Al; Špulák, Marcel; Carmen Catapano, Maria; Mecava, Marko; Prchal, Lukáš; et al.
Graphical abstract: Abstract: Alzheimeŕs disease (AD) is the most common neurodegenerative disorder, characterized by neuronal loss and cognitive impairment. Currently, very few drugs are available for AD treatment, and a search for new therapeutics is urgently needed. Thus, in the current study, twenty-eight new derivatives of montanine-type Amaryllidaceae alkaloids were synthesized and evaluated for their ability to inhibit human recombinant acetylcholinesterase ( h AChE) and butyrylcholinesterase ( h BuChE). Three derivatives (1n, 1o, and 1p ) with different substitution patterns demonstrated significant selective inhibitory potency for h AChE (IC50 < 5 µM), and one analog, 1v, showed selective h BuChE inhibition activity (IC50 = 1.73 ± 0.05 µM). The prediction of CNS availability, as disclosed by the BBB score, suggests that the active compounds in this survey should be able pass through the blood–brain barrier (BBB). Cytotoxicity screening and docking studies were carried out for the two most pronounced cholinesterase inhibitors, 1n and 1v .